Low Level of Innovativeness and the Middle Income Trap – Polish Case Study - Kamil Pruchnik; Jerzy Toborowicz (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The aim of this paper was to verify whether Poland managed to avoid or still might fall into the middle income trap. The paper provides a literature overview concerning the middle income trap. Though there are diverging interpretations of the notion of middle income trap, common conclusions of economists emphasize the importance of innovation-based transformation of economies as a way of avoiding the trap. Further, the paper overviews literature concerning public policies which support this much-needed transformation. We conclude that countries such as Finland, Israel or the USA implemented well-designed top-down economic strategies, which promoted the development of innovations and established effective implementation agencies. Exceptions from this model are some resource rich countries, which managed to avoid the middle income trap without the implementation of such policies, but these countries face in most cases the danger of falling into another trap, called ‘the Dutch disease’. In a subsequent part of the article, we attempt to apply the middle income trap concept to Poland and conclude that it is not possible to clearly state whether Poland avoided the trap or not. This is followed up by a literature-based review of the most common obstacles to innovativeness in Poland. The current growth engines might not be sufficient to ensure economic growth fast enough to speed up the catching up with the most developed countries.